CONSUMER ACCEPTANCE OF ELECTRONIC PURSES AS A PAYMENT FOR LOW VALUE TRANSACTIONS - van der Leij, Sybren (My University, 2011)
The purpose of this research was to determine whether electronic purse (e-purse) schemes could be positioned as alternatives to existing payment methods for low value transactions. The focus was on low value transactions since it was widely believed that this was the area for which e-purse schemes were best suited. The existing payment methods considered in this research included:  Credit Cards  Debit Cards  Cheques  Cash Conjoint analysis was used to analyse the contribution made by various attributes associated with payment methods towards the overall perception of the payment methods by consumers. It was determined that the cost of a transaction and the security the payment method offered against theft, were by far the most important requirements for the likely adoption of a payment method. This implied that PIN protected e-purse schemes were well suited for the low value transaction market.
MBA thesis - WBS
Keywords: Consumer behaviour; Electronic payments; Banks and banking